PENGEMBANGAN KECERDASAN EMOSIONAL PESERTA DIDIK DALAM KONSELING PERORANGAN DI SMA 11 PADANG - Simamora, Priska Mariana; Kasih, Fitria; Gusneli, Gusneli (Bimbingan dan Konseling, 2013)
This research based on the phenomenon that occurred in the field of learners irritability if asked by the teacher supervising the situation himself. The researchers raised the issue with the title Developing Emotional Intelligence of Students in Individual Counseling in SMA 11 Padang. The purpose of this research describe: 1) The form of negative emotions that arise in the students individual counseling. 2) The positive emotions that arise in individual counseling. 3) How the development of emotional intelligence of students in individual counseling. This research was a descriptive quantitative research, the population was students of SMA Negeri 11 Padang who has done individual counseling .Instrument that used was a questionnaire and data analysis techniques using percentage analysis .The results showed that: 1) The form of positive emotions learners appeared quite well with the percentage of 40.83, %. 2) The negative emotions of students who appeared quite well with the percentage of 53.33 %, and 3) How the development of emotional intelligence in counseling individual students quite well with the percentage of 63.33 %.